CHOLINE CHLORIDE BASED NATURAL DEEP EUTECTIC SOLVENTS FOR THE SELECTIVE EXTRACTION OF HESPERIDIN FROM ORANGE PEEL WASTE: A REVIEW - Azhar, Aqil Maulana (Jurnal Chemurgy, 2026)
Industrial citrus processing generates massive volumes of by-products, including peels and seeds, which are rich sources of the bioactive flavonoid hesperidin. This study utilizes a review of Scopus-retrieved secondary data to evaluate the effectiveness of choline chloride-based natural deep eutectic solvents (NADES) for selective hesperidin recovery. Results indicate that specific NADES formulations can outperform traditional organic solvents in yield, while polyol-based hydrogen bond donors provide superior recovery and long-term stability for hesperidin compared to acidic alternatives. Extraction performance is optimized by managing solvent viscosity and mass transfer through a controlled water content of 20% to 30% (w/w) and temperatures between 50°C and 80°C. Finally, high recyclability and retention rates exceeding 96% over multiple cycles demonstrate the economic and environmental feasibility of these green solvents, supporting the transition toward a sustainable circular bioeconomy.